INFLUENCE OF VARIOUS FACTORS ON THE CULTIVATION OF SEEDLINGS IN THE GREENHOUSE (Academicia Globe: Inderscience Research, 2021)
Greenhouses are the most advanced type of building in which crops can be grown with the help of modern engineering tools to create optimal conditions for growing plants. The role of greenhouses is to grow crops off-season, as well as to grow seedlings for protected and open ground. In the past, seedlings were often grown in biologically heated greenhouses and nurseries. Today, seedlings for the open ground are grown mainly in heated film greenhouses, and in backyards and backyards in small film-heated greenhouses in film greenhouses.